(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study explores an integrated approach to diagnosing and treating ocular adnexal tumors (OATs) using molecular genetic testing as a key diagnostic and prognostic tool. OATs, including lymphomas, sebaceous carcinomas, and adenocarcinomas, represent a diverse group of malignancies with variable clinical courses. Traditional histopathological methods often fail to reveal the full molecular complexity of these neoplasms, leading to delayed diagnosis or suboptimal treatment strategies. The inclusion of molecular genetic profiling allows for identification of tumor-specific mutations, chromosomal rearrangements, and biomarkers that guide targeted therapies and predict treatment response. By analyzing 62 patients with histologically confirmed OATs, the research demonstrates that genetic testing substantially enhances diagnostic precision, optimizes treatment selection, and improves overall outcomes. Integration of molecular diagnostics with personalized therapy protocols reduces recurrence rates and supports evidence-based management in ophthalmic oncology. The study presents an in-depth exploration of the clinical and molecular genetic basis for developing a personalized treatment approach in patients with ocular adnexal tumors (OATs). The research integrates advanced molecular diagnostic tools, such as next-generation sequencing (NGS) and gene expression profiling, with clinical data to identify genetic mutations that determine tumor aggressiveness, therapeutic resistance, and patient prognosis. A total of 62 patients diagnosed with OATs underwent a comprehensive evaluation combining histopathological analysis with genetic profiling. Results revealed a high prevalence of mutations in TP53, MYC, BCL2, and KRAS genes, each correlating with distinct histological subtypes and clinical outcomes. The incorporation of molecular genetic testing allowed for individualized treatment plans, including targeted therapy and immunotherapy, thereby improving overall survival rates and reducing recurrence. The findings emphasize the value of integrating molecular data into ophthalmologic oncology to ensure precision-based management, optimized treatment selection, and improved quality of life for affected patients.